Investigation of antioxidant effect of melatonin against carbon tetrachloride toxicity in various tissues - Dönder, Emir; Baydas, Giyasettin; Özkan, Yusuf; Erçel, Ergül; Yalniz, Mehmet; Do?an, Halil (My University, 1999)
Carbon tetrachloride (CCl4) causes lipid peroxidation in various tissues, especially in the liver. The pineal hormone melatonin (Mlt) synthesizes during the night in the pineal gland and has potent antioxidant activity. The aim of this study is to investigate antioxidont effect of melatonin against carbon tetrachloride toxicity in various tissues. In this study, a total of 43 Wistar-Albino rats were studied (CCl4 group = 13 rats, CCl4 + Mit group = 18 rats, and Control group = 12 rats). CCl, after mixed with olive oil at a ratio of 3 / 4 (v/v), was injected subcutaneously at a dose of 0.2 cc/100 g for 10 days. In the CCl4 + Mlt group melatonin was injected subcutaneously at a dose of 10mg / Kg per day. In all groups plasma and tissues lipid peroxidation (as MDA + conjugated dienes) levels were determined. According to the control group, the levels of Malondialdehyde (MDA) and conjugated dienes in plasma, brain, liver and kidney were significantly high in CCl4 group. According to the carbon tetrachloride group, melatonin significantly decreased lipid peroxide levels of plasma and tissues. Melatonin also increased glutathione peroxidase activity (a potent antioxidant anzyme) in the plasma, brain and liver. We conclude that melatonin decreases lipid peroxide level especially in the brain tissue and plasma directly and by increasing glutathione peroxidase activity. Thus, melatonin probably has a vital role for the brain tissue.
Keywords: GSH-Px; Lipid peroxidation; Melatonin